2018
DOI: 10.1155/2018/7246964
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mechanical Compression Device and Supraglottic Airway on Flow Time: A Simulation Study of Out-of-Hospital Cardiac Arrest in a High-Rise Building

Abstract: High-rise buildings present unique challenges to providing high-quality CPR. We investigated the effect of using a mechanical compressor and supraglottic airway on flow time and CPR quality in simulated cardiac arrests occurring within a high-rise building. Twelve teams of EMS providers performed CPR according to 4 scenarios: manual compression and ventilation through bag-valve-mask (MAB) or supraglottic airway (MAS); mechanical compression and ventilation through bag-valve-mask (MEB) or supraglottic airway (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Given the poorer outcomes of OHCA patients from high-rise settings and poorer quality of prehospital interventions, some studies have attempted to look at solutions to address these issues. Six manikin trials compared the use of mechanical CPR (mCPR) with manual compressions during scenario-based resuscitative procedures in high-rise settings [ 11 , 12 , 15 , 21 , 23 , 28 ]. Four of these trials reported positive findings for mCPR where its use led to higher chest compression fractions and greater proportions of guideline-compliant chest compression rate and depth [ 11 , 12 , 15 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation